Efficacy of Endocuff-assisted colonoscopy in the detection of colorectal polyps - Wada, Yoshiki (Endosc Int Open, 2018)
BACKGROUND AND STUDY AIMS : Colonoscopy is the gold standard for detecting colorectal adenomas and cancers. Endoscopic surveillance has been shown to be effective for preventing colorectal cancer. Although detection of colorectal polyps at an early stage is important, endoscopic visualization of early neoplasia can be difficult. The Endocuff is a new device that can be attached to the tip of the colonoscope to hold the colonic folds away from the field of view during withdrawal. The aim of this study was to compare the adenoma detection rate (ADR) and the mean number of adenomas detected per patient (MAP) achieved using Endocuff-assisted colonoscopy (EAC) and standard colonoscopy (SC). PATIENTS AND METHODS : This randomized prospective study was conducted at two academic endoscopy departments in Japan. A total of 447 patients underwent a complete colonoscopic examination between April 2015 and September 2015. The EAC group included 239 patients. The cecal intubation rate, insertion time, withdrawal time, pain score, complications, polyp detection rate (PDR), ADR, the mean number of polyps detected per patient (MPP), and the MAP were assessed. RESULTS : There were no differences between the EAC and SC groups in terms of cecal intubation rate, insertion time, withdrawal time, or pain scores. The PDR in patients increased by about 12 % (61.9 % vs. 49.2 %, P  = 0.013) and ADR increased by 15 % (52.5 % vs. 39.2 %, P  = 0.001) with the use of the Endocuff. The advanced ADR was higher in the EAC group but no statistically significant difference was found (7.7 % vs. 4.6 %, P  = 0.17). Both MPP and MAP were also higher in the EAC group (mean ± SD: 1.33 ± 1.43 vs. 0.83 ± 0.99 per patient; P  < 0.01, 1.11 ± 1.41 vs. 0.66 ± 0.99 per patient; P  < 0.01, respectively). No major complications occurred. CONCLUSIONS:  EAC not only enabled a higher ADR but also significantly increased the mean number of adenomas identified per patient, as compared with SC.